A phase 2 trial of R1507, a monoclonal antibody to the insulin‐like growth factor‐1 receptor (IGF‐1R), in patients with recurrent or refractory rhabdomyosarcoma, osteosarcoma, synovial sarcoma, and other soft tissue sarcomas: Results of a Sarcoma Alliance for Research Through Collaboration study. Issue 16 (2nd May 2014) - Pappo, Alberto S.; Vassal, Gilles; Crowley, John J.; Bolejack, Vanessa; Hogendoorn, Pancras C. W.; Chugh, Rashmi; Ladanyi, Marc; Grippo, Joseph F.; Dall, Georgina; Staddon, Arthur P.; Chawla, Sant P.; Maki, Robert G.; et al.
Abstract : BACKGROUND: Insulin‐like growth factor‐1 receptor (IGF‐1R) is implicated in the pathogenesis of rhabdomyosarcoma (RMS), osteosarcoma (OS), and synovial sarcoma (SS). The authors conducted a multi‐institutional phase 2 trial of the monoclonal antibody R1507 in patients with various subtypes of recurrent or refractory sarcomas. METHODS: Eligibility criteria included age ≥2 years and a diagnosis of recurrent or refractory RMS, OS, SS, and other soft tissue sarcomas. Patients received a weekly dose of 9 mg/kg R1507 intravenously. The primary endpoint was the best objective response rate using World Health Organization criteria. Tumor imaging was performed every 6 weeks × 4 and every 12 weeks thereafter. RESULTS: From December 2007 through August 2009, 163 eligible patients from 33 institutions were enrolled. The median patient age was 31 years (range, 7‐85 years). Histologic diagnoses included OS (n = 38), RMS (n = 36), SS (n = 23), and other sarcomas (n = 66). The overall objective response rate was 2.5% (95% confidence interval, 0.7%‐6.2%). Partial responses were observed in 4 patients, including 2 patients with OS, 1 patient with RMS, and 1 patient with alveolar soft part sarcoma. Four additional patients (3 with RMS and 1 with myxoid liposarcoma) had a ≥50% decrease in tumor size that lasted for <4 weeks. The median progression‐free survival was 5.7 weeks, and the median overall survival was 11 months. The most common grade 3/4 toxicities were metabolic (12%), hematologic (6%), gastrointestinal (4%), and general constitutional symptoms (8%). CONCLUSIONS: R1507 is safe and well tolerated but has limited activity in patients with recurrent or refractory bone and soft tissue sarcomas. Additional studies to help identify the predictive factors associated with clinical benefit in selected histologies such as RMS appear to be warranted. Cancer 2014;120:2448–2456 . © 2014 American Cancer Society . Abstract : R1507 is safe and well tolerated but has limited activity in patients with recurrent or refractory bone and soft tissue sarcomas. Additional studies to help identify predictive factors associated with clinical benefit in selected histologies, such as rhabdomyosarcoma, appear to be warranted.